Evaluation of the agreement of two oscillometric blood pressure devices with invasive blood pressure in anaesthetized chimpanzees (Pan troglodytes). (September 2021) - Moittié, Sophie; Dobbs, Phillipa; Redrobe, Sharon; Liptovszky, Mátyás; White, Kate
Abstract: Objective: To evaluate the agreement of two noninvasive blood pressure devices: a human device with the cuff placed on the wrist (Omron R1) and a veterinary device with the cuff placed on the upper brachium (Surgivet Advisor Vital Signs Monitor) with invasive blood pressure (IBP) measurement in anaesthetized chimpanzees. Study design: Prospective clinical study. Animals: A convenience sample of 11 adult chimpanzees undergoing anaesthesia for translocation and routine health checks. Methods: Systolic (SAP) and diastolic arterial pressures (DAP) were continuously recorded via a transducer connected to a femoral artery cannula, and at 5 minute intervals from the two oscillometric devices. Agreement was explored using Bland-Altman analysis and bias defined as the mean difference between the two measurement methods. Spearman correlation coefficients were calculated. Significance was set at p < 0.05. Results: Bias and standard deviation for the Surgivet compared with IBP were 8.6 ± 18 for SAP and 8.4 ± 9.9 for DAP, showing a significant underestimation of both variables. Limits of agreement (LOA) were from –27 to 44 for SAP and from –11 to 28 for DAP. Correlation coefficients between the Surgivet and IBP values were 0.86 for SAP and 0.85 for DAP ( p < 0.0001). Bias and standard deviation for the Omron compared with the IBP were –21 ± 25 for SAP and –18 ± 15 for DAP, showing a significant overestimation of both variables. LOA were from –70 to –28 for SAP and from –47 to 11 for DAP. Spearman correlation coefficients between the Omron and IBP values were 0.64 for SAP and 0.72 for DAP ( p < 0.0001). Conclusions and clinical relevance: Although neither device met all the criteria for device validation, the Surgivet presented better agreement with IBP values than the Omron in adult anaesthetized chimpanzees.